Absence of mTOR Inhibitor Effect on Hepatic Cyst Growth: A Case Report of a Kidney Transplant Recipient with Autosomal Dominant Polycystic Kidney Disease. (13th December 2012) - Friedrich, L.; Barbey, F.; Pascual, M.; Venetz, J.-P.
Abstract : Some experimental studies have suggested a beneficial effect of the mammalian target of rapamycin (mTOR) inhibitor use on hepatic and renal cyst growth in patients with autosomal dominant polycystic kidney disease (ADPKD). However, the results of clinical studies are conflicting and the role of mTOR inhibitors is still uncertain. We report the case of a patient with ADPKD who underwent deceased kidney transplantation because of an end-stage renal disease. The evolution was uneventful with an excellent graft function under cyclosporine (CsA) monotherapy. Some years later, the patient developed a symptomatic hepatomegaly due to growth of cysts. CsA was replaced by sirolimus, an mTOR inhibitor, in order to reduce or control the increase in the cyst and liver volume. Despite the switch, the hepatic volume increased by 25% in two years. Finally sirolimus was stopped because of the lack of effect on hepatic cyst growth and the presence of sirolimus side effects. The interest of our case resides in the followup by MRI imaging during the mTOR inhibitor treatment and 15 months after the restart of the initial immunosuppressive therapy. This observation indicates that mTOR inhibitors did not have significant effect on cyst-associated hepatic growth in our patient, which is consistent with some results of recent large clinical studies.